Micro‐Raman and SER spectroscopy to unfold Lefranc's early organic pigment formulations. (17th October 2016) - Gabrieli, F.; Doherty, B.; Miliani, C.; Degano, I.; Modugno, F.; Uldank, D.; Kunzelman, D.; Buzzegoli, E.; Patti, M.; Rosi, F.
Abstract : The introduction of synthetic dyes and pigments into commerce in the late 19th century was a stimulating time for experimental scientists in their laboratory formulations and for artists in their usage. Nowadays, the period of pioneering syntheses and employment of synthetic organic colouring materials is highly intriguing for scientific research and for conservation purposes in heritage science. In this work, a combination of spectroscopic and chromatographic methods has permitted the elucidation of the chemical composition of 16 early synthetic organic pigment powders from the Lefranc experimental laboratory collection dating 1890–1914. It can be hypothesized that the most successful of these formulations could have been finalized in paint tubes and released onto the market, meaning that they may even be found in artworks from the same period. Specifically, information from this crucial period of transition from the exclusive use of natural dyes/colourants (such as neoflavonoids and plant and insect anthraquinones) to the introduction of their synthetic counterparts (such as synthetic alizarin and purpurin, and acid stable cochineal, together with monoazo and diazo pigments) is confirmed through Raman/surface‐enhanced Raman spectroscopy and high‐performance liquid chromatography with diode array detection. By means of X‐ray fluorescence and mid‐Fourier transform infrared spectroscopy, a combination of traditional and modern inorganic substrates has been identified (alum, kaolin, barium sulfate and metallic salts), while Raman has provided additional data regarding the possible complexation of these pigments in the form of lakes. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In this work, combined Raman and chromatography techniques have been utilized to probe organic pigment constituents of 16 in‐house Lefranc experimental formulations. Highlighted use of natural neoflavonoids, anthraquinones, and synthetic azo pigments and mixtures provides a greater understanding of early laboratory syntheses for heritage science purposes.